Pigeonpea Hybrid-Proline-Rich Protein (CcHyPRP) Confers Biotic and Abiotic Stress Tolerance in Transgenic Rice - Mellacheruvu, Sunitha; Tamirisa, Srinath; Vudem, Dashavantha Reddy; Khareedu, Venkateswara Rao (Frontiers in Plant Science, 2016)
In this study, we report the overexpression of Cajanus cajan hybrid-proline-rich protein encoding gene (CcHyPRP) in rice which resulted in increased tolerance to both abiotic and biotic stresses. Compared to the control plants, the transgenic rice lines, expressing CcHyPRP, exhibited high-level tolerance against major abiotic stresses, viz., drought, salinity and heat, as evidenced by increased biomass, chlorophyll content, survival rate, root and shoot growth. Further, transgenic rice lines showed increased panicle size and grain number compared to the control plants under different stress conditions. The CcHyPRP transgenics, as compared to the control, revealed enhanced activities of catalase and superoxide dismutase (SOD) enzymes and reduced malondialdehyde (MDA) levels. Expression pattern of CcHyPRP::GFP fusion-protein confirmed its predominant localization in cell walls. Moreover, the CcHyPRP transgenics, as compared to the control, exhibited increased resistance to the fungal pathogen Magnaporthe grisea which causes blast disease in rice. Higher levels of bZIP and endochitinase transcripts as well as endochitinase activity were observed in transgenic rice compared to the control plants. The overall results demonstrate the intrinsic role of CcHyPRP in conferring multiple stress tolerance at the whole-plant level. The multipotent CcHyPRP seems promising as a prime candidate gene to fortify crop plants for enhanced tolerance/resistance to different stress factors.